Chaperonin containing TCP-1 (CCT/TRiC) is a novel therapeutic and diagnostic target for neuroblastoma - Cox, Amanda; Nierenberg, Daniel; Camargo, Oscar; Lee, Eunkyung; Khaled, Amr S.; Mazar, Joseph; Boohaker, Rebecca J.; Westmoreland, Tamarah J.; Khaled, Annette R. (Frontiers in Oncology, 2022)
Chaperonin containing TCP1 (CCT/TRiC) is a multi-subunit protein folding complex that enables the cancer phenotype to emerge from the mutational landscape that drives oncogenesis. We and others linked increased expression of CCT subunits to advanced tumor stage and invasiveness that inversely correlates with cancer patient outcomes. In this study, we examined the expression of the second CCT subunit, CCT2, using genomic databases of adult and pediatric tumors and normal tissues, and found that it was highly expressed in pediatric cancers, showing a significant difference compared to normal tissues. Histologic staining confirmed that CCT subunits are highly expressed in tumor tissues, which was exemplified in neuroblastoma. Using two neuroblastoma cells, MYCN-amplified, IMR-32 cells, and non-amplified, SK-N-AS cells, we assessed baseline levels for CCT subunits and found expressions comparable to the highly invasive triple-negative breast cancer (TNBC) cell line, MDA-MB-231. Exogenous expression of CCT2 in both SK-N-AS and IMR-32 cells resulted in morphological changes, such as larger cell size and increased adherence, with significant increases in the CCT substrates, actin and tubulin, as well as increased migration. Depletion of CCT2 reversed these effects and reduced cell viability. We evaluated CCT as a therapeutic target in IMR-32 cells by testing a novel peptide CCT inhibitor, CT20p. Treatment with CT20p induced cell death in these neuroblastoma cells. The use of CCT2 as a biological indicator for detecting neuroblastoma cells shed in blood was examined by spiking IMR-32 cells into human blood and using an anti-CCT2 antibody to identify spiked cancer cells with the CellSearch system. Results showed that using CCT2 for the detection of neuroblastoma cells in blood was more effective than the conventional approach of using epithelial markers like cytokeratins. CCT2 plays an essential role in promoting the invasive capacity of neuroblastoma cells and thus offers the potential to act as a molecular target in the development of novel therapeutics and diagnostics for pediatric cancers.